The effects of positive spillover and work-family conflict on female academics’ psychological well-being - Farradinna, Syarifah; Halim, Fatimah Wati; Sulaiman, Wan Shahrazad Wan (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2019)
The issue of married women who work as academic lecturers is important to be studied. They are demanded to preserve their independence and increase intellectuality which then may decrease when they have children. This study aimed to examine whether positive spillover can reduce work-family or family-work conflict so as to improve psychological well-being. The subjects, who were screened with a random sampling technique, were 429 female lecturers working in universities in Riau. Data were analyzed using descriptive analysis and multiple regression. The result showed that respondents have low psychological well-being and better family-work positive spillover. Multiple regression analysis showed that family-work positive spillover and family-work conflict simultaneously influenced psychological well-being. Therefore, it can be concluded that female lecturers prioritize completing home tasks over others, which reduces their psychological well-being at the workplace.